Prevalence, factors influencing and knowledge about adherence to lipid-lowering therapy among hyperlipidemia patients - Devaraj, Navin Kumar; Mohamed, Mohazmi; Hussein, Norita (Malaysian Medical Association, 2017)
Background: Hyperlipidaemia is a significant risk factor for cardiovascular disease. However, adherence to lipid-lowering therapy is often unsatisfactory due to a combination of patient factors, therapy, socio-economic and health system-related factors. Aims: to identify the prevalence of adherence to lipid-lowering therapy, the factors contributing to non-adherence and knowledge regarding hyperlipidaemia and its’ treatment among Malaysian patients with hyperlipidemia. Methods: A quantitative study using a cross-sectional survey was carried out in an urban primary care clinic in August 2015. Patients on lipid-lowering therapy for ≥ 1 year aged ≥ 18 years were selected using simple random sampling. consenting patients answered a self-administered questionnaire (in Malay/English) which included socio-demographic profile, hyperlipidaemia profile, adherence to lipid-lowering therapy (using the Morisky Medication Adherence scale-8; score ≥ 6 taken as adherent), reasons leading to non-adherence, knowledge regarding hyperlipidaemia and its’ treatment, and use of non-allopathic medicine. Results: the response rate was 90.7%. the prevalence of adherence to lipid-lowering therapy was 82.4%. “the most common reasons for non-adherence was being worried about side effect of lipid-lowering agent (71.4%), followed by the need to take too many drugs in a day (61.4%) and negative influences by friends, relative and mass media (60%)”. Factors associated with non-adherence include male gender, on longer duration of therapy, less frequency of follow-up, less number of follow-up clinics, taking medication at night/random timing and having lower knowledge scores. Conclusion: Overall the prevalence of adherence was high in patients with hyperlipidaemia. Interventions to boost adherence should target those who were identified as non-adherent.